Growing Innovation in Rural Sites of Learning - Schnellert, Leyton; Datoo, Mehjabeen; Kozak, Donna; Miller, Miriam; Giles, Graham (Perspectiva Educacional, 2023)
The implementation of a revised curriculum in British Columbia, Canada’s rural schools and school districts is providing rich opportunities to study and document processes that support and prompt system change, as well to generate knowledge that can be shared across the province and more widely. This project aimed to study closely the practices and structures within BC’s Growing Innovation in Rural Sites of Learning professional learning network (PLN), to examine how this partnership between a university, the Ministry of Education, and the BC Rural Education Advisory is spurring innovation through collaborative, inquiry-based professional learning. This study examined how a PLN can generate and mobilize knowledge related to innovative and effective practice, particularly across rural or remote communities, and the role of PLNs in provoking and sustaining educational innovation. Key findings revealed that innovation occurs when educators find openings and gaps that create space and necessity for change, and that collaboration and reflection are key factors in sustaining and spreading innovation. Key drivers of this change included the new curriculum in BC as well as student learning needs and the challenges of the various rural contexts. Key factors in sustainability included administrative and district support as well as the ability to share their learning, including within the network.